APLIKASI PEMBELAJARAN SEDERHANA PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) BINA MANDIRI MENGGUNAKAN GOOGLE APPSHEET DAN GOOGLE SPREADSHEET - Saepulloh; Fadzar Rusghana (Melati Institute, 2023)
Every year almost all scientific fields are forced to change continuously following the development of technology that continues to experience renewal, as well as the field of education which must continue to strive to keep up with technological developments both from the teacher's side and from the student's side. Bina Mandiri Community Learning Center (PKBM) is one of the educational institutions in which there are learning activities with the Equivalency Education package method consisting of equivalency package A or elementary school, equivalency package B or junior high school and equivalency package C or high school. The material delivery system and attendance process at PKBM Bina Mandiri is still manual so it is less effective. Therefore, a learning application is needed to simplify and streamline the learning process at PKBM Bina Mandiri. This research aims to design and create a simple Learning application using Google Appsheet to be used by PKBM Bina Mandiri so that it makes it easier for teachers and students to carry out the teaching and learning process.